Pengaruh Penerapan Sanksi Pajak dan Tingkat Kepercayaan terhadap Kepatuhan Wajib Pajak : (Pelaku UMKM Kerupuk Desa Tlasih, Sidoarjo) - Dewi Murdiawati (Jurnal Ekonomi Manajemen Akuntansi, 2024)
This study aims to determine the effect of the application of tax penalties, understanding of taxation, tax socialization, and the level of trust on taxpayer compliance of Tlasih Village cracker MSME players. The sample used is 60 respondents. The sampling method use in this study uses saturated sampling. The data in this study were obtained through quisionnaires given directly (offline).. The results showered that the effect of the tax penalties and the level of trust had an effect on taxpayer compliance (Tlasih Village Cracker MSMEs Actors).